A distributed optimization method for urban active distribution networks considering SOPs and user side flexible resources based on ADMM - Chunhe Jia; Botao Huang; Zhiyuan Chuai; Chao Yan; Qingwei Wang; Haolin Li; Song Zhang; Xiangyu Chen (Systems Science & Control Engineering)
The optimal scheduling of the active distribution network (ADN) is increasingly challenging due to the rising risk of ADN operation and the growth of user-side flexible resources, driven by clean energy and home device popularization. The method proposed in this paper utilizes network-side and user-side flexible resources to lower operating costs and raise system performance levels under the consideration of grid demand and user demand. In this study, mathematical models of the soft open point (SOP) and electric water heater were first constructed, and the optimal power flow model of the ADN with dynamic network reconfiguration (DNR) was established. By utilizing second-order cone relaxation (SOCR), the original mixed integer nonlinear problem (MINLP) is converted into mixed-integer second-order cone problem (MISOCP). Finally, considering the privacy of user information, a distributed optimization method for ADN integrated with SOPs and user side flexible resources is proposed based on the alternating direction method of multiplier (ADMM). An IEEE 33 bus system is used to confirm the viability of the proposed approach. The results show that the proposed method can lower the operating cost of the ADN, improve the system voltage quality, and improve system performance.